La relativité culturelle de la victimisation. Quelques réflexions sur les problèmes et le potentiel de la victimologie comparée - Fattah, Ezzat (Criminologie, 1993)
The purpose of the paper is to present some reflexions on the cultural relativity of victimization. It argues against the widely held belief among victimologists that victimization can be universally defined. Like crime, victimization can be seen as a cultural construct. The paper presents many examples illustrating the cultural relativity of victimization. Children's work, child abuse and neglect, violence, abortion, sexual behavior etc. are given as examples to emphasize the variability in the definition from one society to another. The author concludes by proposing comparative research covering various aspects of victimization.